How the policy mix and its consistency impact innovation: Findings from company case studies on offshore wind in Germany - Kristin Reichardt; Karoline Rogge (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
Transforming the energy system to one with a greater importance of renewable power generation technologies requires redirecting and accelerating technological change. In this transition, so-called policy mixes play a crucial role. Yet precisely how policy mixes affect technological innovation remains poorly understood. To remedy this, in this study we choose a qualitative company case study approach to analyze the innovation impact of the elements of a policy mix - its policy strategy and instrument mix - and their consistency. Taking offshore wind in Germany as research case, we find that the German offshore wind policy mix, its consistency and perceived high credibility have been vital innovation drivers. Specifically, its consistent policy strategy and the consistency of the policy strategy with the instrument mix appear crucial to research, development and demonstration. Still, for this emerging technology to be adopted the policy mix seems to require a consistent and comprehensive instrument mix.
urn:nbn:de:0011-n-2942276
Keywords: 330; policy mix; policy strategy; instrument mix; consistency; innovation; off-shore wind